UTANG NEGARA, DIBAYAR OLEH WARGA NEGARA, DAN TINJAUANNYA MENURUT SYARI'AT AGAMA - Eko Saputra; Qurroh Ayuniyyah (Diversity: Jurnal Ilmiah Pascasarjana, 2021)
Debt or in accounting terms is referred to as a liability at the conceptual and implementation level in the Islamic economic system is legal as long as it does not conflict with the principle of halalness and the principle of benefit. however, if the debt uses an interest instrument, the law is haram. Citizens are not obliged to pay off debts taken by the government, but those who are obliged to repay the debts in question are the officials or the government in power or if this is not possible, the next government is responsible for making payments when the mechanisms and processes for the facilities taken are in accordance with the procedures applies. However, if there is a distortion or fraud (deviation), the person obliged to return the debt payment obligation is an individual from the authorized official as the policy maker of the facility